Downregulation of Renal G Protein–Coupled Receptor Kinase Type 4 Expression via Ultrasound‐Targeted Microbubble Destruction Lowers Blood Pressure in Spontaneously Hypertensive Rats. Issue 10 (October 2016) - Huang, Hefei; Li, Xiaolong; Zheng, Shuo; Chen, Yue; Chen, Caiyu; Wang, Jialiang; Tong, Haipeng; Zhou, Lin; Yang, Jian; Zeng, Chunyu
Abstract : Background: G protein–coupled receptor kinase type 4 (GRK4) plays a vital role in the long‐term control of blood pressure (BP) and sodium excretion by regulating renal G protein–coupled receptor phosphorylation, including dopamine type 1 receptor (D1 R). Ultrasound‐targeted microbubble destruction (UTMD) is a promising method for gene delivery. Whether this method can deliver GRK4 small interfering RNA (siRNA) and lower BP is not known. Methods and Results: BP, 24‐hour sodium excretion, and urine volume were measured after UTMD‐targeted GRK4 siRNA delivery to the kidney in spontaneously hypertensive rats. The expression levels of GRK4 and D1 R were determined by immunoblotting. The phosphorylation of D1 R was investigated using immunoprecipitation. The present study revealed that UTMD‐mediated renal GRK4 siRNA delivery efficiently reduced GRK4 expression and lowered BP in spontaneously hypertensive rats, accompanied by increased sodium excretion. The increased sodium excretion might be accounted for by the UTMD regulation of D1 R phosphorylation and function in spontaneously hypertensive rats. Further analysis showed that, although UTMD had no effect on D1 R expression, it reduced D1 R phosphorylation in spontaneously hypertensive rats kidneys and consequently increased D1 R‐mediated natriuresis and diuresis. Conclusions: Taken together, these study results indicate that UTMD‐targeted GRK4 siRNA delivery to the kidney effectively reduces D1 R phosphorylation by inhibiting renal GRK4 expression, improving D1 R‐mediated natriuresis and diuresis, and lowering BP, which may provide a promising novel strategy for gene therapy for hypertension.